NONLINEAR MODEL OF PERSONALITY IS IN CONTEXT OF GLOBALIZE - Кичкирук, Т. В. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The article exposes the nonlinear model of personality in the context of globalize. The new (synergetic) model of personality is offered is an innovative people, the purpose of life of which is become by a self-education, self-determination, stimulant a man on own, yet not discovered possibilities.